The Role of Religion in Hospitality Organization: The Case of Pekalongan Batik Village, Indonesia - Susminingsih, Susminingsih; Kanafi, Imam (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This study aimed to analyze the relationship between religion and Pekalongan Batik Village as a hospitality organization. The existence of Batik Village was very essential, not only for the development of local economics such as employment creation, tourism satisfaction and to generate selling, but also for the religious community development. The government policy to establish the batik village was a good decision to attract more customers and improve competitiveness. In terms of public policy perspective, Batik Village was more effective and efficient for local government to provide technical support, capital and management support, promotion, education and training and many more. Employer and employee, wholesaler, and supplier mostly had close interrelationship (ukhuwwah), mutual respect (tasamuh), understanding (tafahum) and cooperation (ta’awun) and as well as trustworthiness (amanah); and they live in Islamic compliance. The study of how they developed their organization based on hospitality religion was interesting to be observed . This study highlighted the religious contribution of hospitality organization by classifying the followings: (1) The cooperation type of Pekalongan batik village organization, (2) The Islamic socio-cultural contribution understanding in terms of human resource management, innovation, business ethic and marketing behavior. Tujuan dari kajian paper ini adalah untuk menganalisis hubungan antara agama dan Kampung Batik Pekalongan sebagai organisasi yang ramah. Keberadaan Kampung Batik sangat penting, tidak hanya untuk pengembangan ekonomi lokal seperti penciptaan lapangan kerja, kepuasan pariwisata dan untuk menghasilkan penjualan, tetapi juga untuk meningkatkan komunitas agama. Kebijakan pemerintah untuk menegakkan Kampung Batik adalah keputusan yang baik untuk mencari pelanggan dan meningkatkan daya saing. Dari perspektif kebijakan publik, desa batik lebih efektif dan efisien bagi pemerintah daerah untuk memberikan dukungan teknis, modal dan manajemen, promosi, pendidikan dan pelatihan dan banyak lagi lainnya. Sebagian besar majikan dan karyawan, pedagang grosir, dan pemasok memiliki keterkaitan yang erat (ukhuwwah), saling menghargai (tasamuh), saling memahami satu dengan yang lainnya (tafahum), dan mereka memiliki sikap dapat dipercaya (amanah), dan mereka hidup dalam ajaran Islam. Sangat menarik untuk meneliti tentang bagaimana mereka mengembangkan organisasi mereka berdasarkan agama yang ramah. Makalah ini menyoroti kontribusi agama dalam organisasi usaha batik yang ramah dengan mengidentifikasi dalam banyak cara: (1) tipe kerjasama dalam organisasi Kampung batik Pekalongan, (2) mengidentifikasi pemahaman kontribusi sosial-budaya keramahtamahan Islam dalam hal manajemen sumber daya manusia, inovasi, etika bisnis dan perilaku pemasaran